PENGEMBANGAN MATERI KEBERFUNGSIAN KELUARGA BAGI SISWA SMA - Akila, Naisa; ', Rosmawati; Umari, Tri (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2016)
Abstract:The purpose ofthis research is the complete of family function material of class XI senior high school and determine the quality of family function material is resulted, in terms of aspects of clarity, systematics, image support, freshness, completeness of material, and support for video and games. The method of material are research method and the development (R & D). This material is valid by the first and second counselor, the teacher of counseling guidance, as well as 31student of class XI senior high school 12 Pekanbaru. This material tried to students along 3 hours lesson in class( 3x 45’). The result of this research is the compiled material about family function, with the material quality in category “good” with the score aspect 4,09.Key words: The material of counseling guidance, family function.